FAKE : FAKE MONEY, FAKE TEACHERS, FAKE ASSETS : HOW LIES ARE MAKING THE POOR AND MIDDLE CLASS POORER - Kiyosaki, Robert, 1947-
The author uses his perspectives and insights into financial events and crises in his lifetime as well as references drawn from Dr. R. Buckminster Fuller's 1983 work, Grunch of giants and Steven Brill's May 28, 2018 Time magazine article to illustrate